Emerging Trends in Malignant Hyperthermia; Uncommon Yet Increasingly Seen in the Indian Subcontinent - Sonal S. Khatavkar; Subha T. Jose Vazhakalayil; Sandeep D. Veer; Jekha M. Babu (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2025)
This study presents a rare occurrence of malignant hyperthermia (MH) within our hospital setting, making it the first instance in 25 years. It might possibly be the first case confirmed through genetic testing in western India. The case involves a young female undergoing scoliosis correction surgery, whose life was lost despite immediate supportive interventions. The incident underscores the imperative of readily accessible dantrolene, the drug of choice for MH, and emphasizes the significance of case reporting in the absence of a national registry for MH in India, thereby augmenting awareness of this infrequent yet potentially fatal condition.